2017
DOI: 10.1515/rmzmag-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric rolling process

Abstract: Asymmetric rolling is a novel technique used to control both the texture and the grain refinement of metallic materials. The aim of asymmetric rolling is to apply a large shear strain uniformly through the thickness of the plate, by maintaining a high degree of friction between the sheet and the rolls. It can be used to improve the formability of material. One of the advantages of asymmetrical rolling is that the rolling force and torque can be decreased. The methods used for the asymmetric rolling are single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…They revealed that AR applied after CR reduces basal texture density and improves mechanical properties (Cho et al 2013). Also, a lower rolling force by almost half and lower torque is another advantage of AR compared to CR (Fajfar et al 2017;Kiefer and Kugi 2008;Liu and Kawalla 2012;Orlov et al 2013;Vincze et al 2020).…”
Section: The Principles Of Asymmetrical Rollingmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that AR applied after CR reduces basal texture density and improves mechanical properties (Cho et al 2013). Also, a lower rolling force by almost half and lower torque is another advantage of AR compared to CR (Fajfar et al 2017;Kiefer and Kugi 2008;Liu and Kawalla 2012;Orlov et al 2013;Vincze et al 2020).…”
Section: The Principles Of Asymmetrical Rollingmentioning
confidence: 99%
“…According to their mathematical and computer modeling, the closer the shape factor, calculated by the ratio of contact arc length to average thickness in asymmetric rolling, is to 1.8, the straighter the material will come out. Material curvature in AR can also be eliminated by equipping the rolling mill with a table roller (Fajfar et al 2017;Kiefer and Kugi 2008). The difference in rolls' speeds and the percentage of thickness reduction affect the curvature tendency.…”
Section: The Principles Of Asymmetrical Rollingmentioning
confidence: 99%
“…In addition, intentional and controlled asymmetry was introduced into the rolling process, the source of which can be a variation in the diameter or speed of the rolls, a variation in the value of the friction coefficients, as well as a change in the angle of feed [11][12][13][14]. Asymmetry in the rolling process introduces additional shear stresses into the material, which result in reduced forces during rolling, increased rolling reduction in one rolling pass, as well as the curvature of the strip in the longitudinal direction to the rolling direction [15][16][17][18][19][20][21]. During the conducted tests, asymmetry resulting from different rolling speeds and from the variation of the friction coefficients between the rolls was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…This type of extrusion belongs to the large group of SPD methods extensively described in the literature for the processing of various materials, but in contrast to previously described methods also enables the fabrication of rods with cross sections of various shapes and sizes. The SPD methods that are most frequently used and described in the literature are: equal channel angular extrusion [22][23][24], high-pressure torsion [25][26][27], accumulative roll bonding [28][29][30], repetitive corrugation and straightening [31][32][33], and asymmetric rolling [34][35][36]. The aim of all of them is the intense refining of the metal grain size in order to obtain superior mechanical properties.…”
Section: Introductionmentioning
confidence: 99%